Neuroradiologic Evaluation of Joubert's Syndrome: Case Report - Yıldırım, Hanefi; Murat, Ayşe; Aydın, Mustafa; Benzer, Derya (Fırat University, 2005)
Joubert syndrome is a rare autosomal recessive disorder characterized by abnormal respiratory pattern and eye movements, hypotonia, ataxia, developmental retardation with neuropathologic abnormalities of cerebellum and brainstem. We aimed to point out the clinical heterogenity and radiologic findings of JS. We presented a case of Joubert syndrome associated with ptosis and hypotonia.©2005, Fırat Üniversitesi, Tıp Fakültesi

Joubert sendromu anormal solunum düzeni ve göz hareketleri, hipotoni, ataksi, serebellum ve beyin sapının nöropatolojik anomalileri ile birlikte gelişimsel geriliğin olduğu, nadir görülen otozomal resesif bir sendromdur. Pitozis ve hipotonisite yakınması ile başvuran bir Joubert sendromu olgusu sunularak, literatür bilgileri ışığında, sendromun klinik heterojenitesi ve radyolojik bulgularını sunmayı amaçladık. ©2005, Fırat Üniversitesi, Tıp Fakültesi
Joubert Sendromunun Nöroradyolojik Açıdan Değerlendirilmesi: Olgu Sunumu